A description of the development of HR Tech startups in Poland - Natalia Mańkowska; Katarzyna Kamińska (Scientific Journal of Gdynia Maritime University, 2021)
This article presents the problem of development and survival of startups providing services in the field of human resources. Research on startup success factors indicates that many variables simultaneously determine the possibility of survival in the market. The data used for the analysis were sourced from the website: www.mamstartup.pl (a database of startups established in Poland) and other publicly available data. The results of the analysis indicate that HR Tech is an industry that includes specific services for entrepreneurs, employees, or labour market participants in general. In the period surveyed (2012–2020) about 44% of startups from this industry in Poland ceased their activities. There is a lack of detailed, publicly available data on their funding. The startups under study use business models focused on generating revenue from the user of a given IT solution. The analysis shows that the survival and development of HR Tech startups in Poland is quite difficult; the problem is probably the specificity of services and their questionable profitability in the industry studied.